2003
DOI: 10.1063/1.1598282
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of confined states in metallic single-walled carbon nanotubes

Abstract: We investigated the local density of states ͑LDOS͒ of extended individual metallic single-walled carbon nanotubes using low-temperature scanning tunneling spectroscopy. We observed that the LDOS oscillates with energy close to the Fermi level. The oscillation period of about 50 meV varies with position on the nanotube. Maps of the LDOS reveal that the peaks in the oscillation are related to confined states. The widths of the peaks increase with increasing distance from the Fermi level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 20 publications
(15 reference statements)
0
36
0
Order By: Relevance
“…Various defects in CNTs are widely observed in experiments. 23,24 We chose a section of a (5, 5) SWNT to study the change in stability of defects as a function of their distance from the open end of the nanotube. As shown in panel 0…”
Section: Methods Of the Theoretical Studymentioning
confidence: 99%
“…Various defects in CNTs are widely observed in experiments. 23,24 We chose a section of a (5, 5) SWNT to study the change in stability of defects as a function of their distance from the open end of the nanotube. As shown in panel 0…”
Section: Methods Of the Theoretical Studymentioning
confidence: 99%
“…Moreover, defects in SWNTs have been shown to be useful for achieving the desired functionality. In particular, it was demonstrated that intrinsic defects in metallic SWNTs embodied in source-drain-gate devices can provide resonant backscattering characteristics 8,9 leading to low-temperature quantum dot devices, as well as a high gate sensitivity at the defect position. 10 Thus, the knowledge of how and to which extent different types of defects can change the electronic properties of SWNTs is important, as it may open a route toward controllable engineering of the properties of SWNT-based electronic devices or even result in the appearance of a different class of devices with the properties entirely designed by a controlled creation of particular defects.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the properties of these defects has become an essential part of such diverse processes in carbon materials such as strain, 1 lithium storage in nanotube based batteries, 2 catalytic growth, 3 junctions, 4 and quantum dot creation. 5,6 Studies of radiation effects 7 in graphite and other carbon nanostructures and experiments on as-grown nanotubes 5,8 have demonstrated that intrinsic carbon defects are a common phenomenon in standard samples. One of the most common intrinsic defects created is the carbon vacancy-adatom pair, 7 and therefore it is important to study the influence this kind of defect will have on the surface physical and electronic structure.…”
Section: Introductionmentioning
confidence: 99%